A Nearly Packaging‐Free Design Paradigm for Light, Powerful, and Energy‐Dense Primary Microbatteries. Issue 35 (19th July 2021) - Yue, Xiujun; Johnson, Alissa C.; Kim, Sungbong; Kohlmeyer, Ryan R.; Patra, Arghya; Grzyb, Jessica; Padmanabha, Akaash; Wang, Min; Jiang, Zhimin; Sun, Pengcheng; Kiggins, Chadd T.; Ates, Mehmet N.; et al.
Abstract: Billions of internet connected devices used for medicine, wearables, and robotics require microbattery power sources, but the conflicting scaling laws between electronics and energy storage have led to inadequate power sources that severely limit the performance of these physically small devices. Reported here is a new design paradigm for primary microbatteries that drastically improves energy and power density by eliminating the vast majority of the packaging and through the use of high‐energy‐density anode and cathode materials. These light (50–80 mg) and small (20–40 µL) microbatteries are enabled though the electroplating of 130 µm‐thick 94% dense additive‐free and crystallographically oriented LiCoO2 onto thin metal foils, which also act as the encapsulation layer. These devices have 430 Wh kg −1 and 1050 Wh L −1 energy densities, 4 times the energy density of previous similarly sized microbatteries, opening up the potential to power otherwise unpowerable microdevices. Abstract : Billions of internet‐connected devices require microbattery power sources, but their operating times are severely limited by the poor scaling of battery energy density. This work presents a new design paradigm for primary microbatteries that drastically improves energy and power density by eliminating the majority of packaging and using thick and dense electrodes with controlled crystal orientation for fast transport.